2009
DOI: 10.1172/jci36433
|View full text |Cite
|
Sign up to set email alerts
|

Self-regulation of inflammatory cell trafficking in mice by the leukocyte surface apyrase CD39

Abstract: Leukocyte and platelet accumulation at sites of cerebral ischemia exacerbate cerebral damage. The ectoenzyme CD39 on the plasmalemma of endothelial cells metabolizes ADP to suppress platelet accumulation in the ischemic brain. However, the role of leukocyte surface CD39 in regulating monocyte and neutrophil trafficking in this setting is not known. Here we have demonstrated in mice what we believe to be a novel mechanism by which CD39 on monocytes and neutrophils regulates their own sequestration into ischemic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
81
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 106 publications
(93 citation statements)
references
References 57 publications
(92 reference statements)
7
81
0
Order By: Relevance
“…Hyman et al have recently shown that CD39 on both endothelial cells and leukocytes reduces inflammatory cell trafficking and platelet reactivity following cerebral ischemia [31]. CD39 is also protective in cerebrovascular ischemia [32] and soluble CD39 infusion can restore postischemic cerebral perfusion [32].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Hyman et al have recently shown that CD39 on both endothelial cells and leukocytes reduces inflammatory cell trafficking and platelet reactivity following cerebral ischemia [31]. CD39 is also protective in cerebrovascular ischemia [32] and soluble CD39 infusion can restore postischemic cerebral perfusion [32].…”
Section: Discussionmentioning
confidence: 99%
“…31 P NMR All experiments were performed at a 31 P Frequency of 145.7 MHz (360 MHz for 1 H) on a, 9-cm vertical bore, Bruker DRX (Burker Biospin Inc. Bellerica, MA) spectrometer. Mice were anesthetized with a mixture of Ketamine/ Xylazine (100 mg and 10 mg/kg) and the liver was surgically exposed.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations